Anemia before and during concurrent chemoradiotherapy in patients with cervical carcinoma: Effect on progression-free survival. Issue 5 (1st August 2003) - Obermair, A.; Cheuk, R.; Horwood, K.; Neudorfer, M.; Janda, M.; Giannis, G.; Nicklin, J. L.; Perrin, L. C.; Crandon, A. J.
Abstract : To determine the impact of anemia before and during chemoradiation in patients with cervical cancer, we collected data on hemoglobin (Hb) levels before and during treatment from 60 unselected patients with cervical carcinoma. All patients had FIGO stage IB to IVA disease and were treated with concurrent chemoradiation for the aim of cure. Patients with an Hb value below or equal to the lower 25th quartile were considered anemic. Progression-free survival (PFS) was evaluated by univariate and multivariate analyses. After a median follow-up of 26.3 months, 20 patients developed disease progression. The lowest Hb during chemoradiation (nadir Hb), the stage of disease, and parametrial involvement were correlated significantly with PFS. On multivariate analysis, the nadir Hb (relative risk [RR] 0.29) and tumor stage (RR 3.4) remained the only prognostically relevant factors predicting PFS. At 60 months the PFS was 39.1% for anemic patients and 48.0% for nonanemic patients ( P < 0.0002). In patients undergoing chemoradiation for cervical carcinoma, a low nadir Hb is highly predictive of shortened PFS, whereas the Hb before treatment is prognostically not significant.